一种舰载雷达有源干扰系统效能评估方法 (2025)
本发明公开了一种舰载雷达有源干扰系统效能评估方法，包括：S1：构建雷达有源干扰效能评估指标体系；S2：获取所述准则层下的指标的主观权重；S3：获取所述准则层下的指标的客观权重；S4：获取归一化后的组合权重向量；S5：对所述雷达有源干扰效能评估指标体系进行评估。本发明在构建雷达有源干扰效能评估指标体系的基础上，利用主观赋权方法和客观赋权方法进行组合赋权，结合Vague集，对所述雷达有源干扰效能评估指标体系进行评估，充分利用了Vague集处理模糊问题和组合赋权求解权重的优势，实现舰载雷达有源干扰系统效能的可靠评估，使评估结果更加真实可靠。提高舰载雷达有源干扰系统效能评估的实用性。 The invention discloses a ship-borne radar active jamming system efficiency evaluation method. The method comprises the following steps: S1, constructing a radar active jamming efficiency evaluation index system; s2, obtaining subjective weights of indexes under the criterion layer; s3, obtaining objective weights of the indexes under the criterion layer; s4, obtaining a combined weight vector after normalization; and S5, evaluating the radar active interference efficiency evaluation index system. According to the method, on the basis of constructing the radar active interference effectiveness evaluation index system, the subjective weighting method and the objective weighting method are used for combined weighting, the ra